The Digital Journey of Regional Linguistic Identity - Dr. Rahul Mhaiskar, (Indian Journal of Management and Language (IJML), 2025)
Varhadi and Nagpuri Marathi, key varieties spoken in the Vidarbha region of the State of Maharashtra, are thriving in the digital space, bridging traditional oral culture with modern technology. This study examines the representation of variety across various platforms, including YouTube, Facebook, Instagram, and WhatsApp, as well as contributions from regional cinema and mobile apps. Data analysis highlights content categories such as comedy, lifestyle, tourism, education, and political discourse, with creators like Neha Thombre, Shashank Udakhe and Karale’s Phoenix Academy Wardha gaining significant traction. Films like Naal and shows like Fu Bai Fu, Chala Hava Yeu Dya, and Maharashtrachi Hasya Jatra showcase the authentic Varhadi Marathi character played by Marathi Actor Bharat Ganeshpure, while apps like the Varhadi Bible cater to cultural and religious contexts. Messaging platforms further enhance variety presence, enabling informal communication and cultural exchange. This research highlights how regional languages utilise digital media to preserve linguistic identity, foster cultural richness, and engage broader audiences, underscoring the potential of regional varieties to thrive in the era of digital transformation.